Zataria multiflora Boiss.: A review study on chemical composition, anti-fungal and anti-mycotoxin activities, and ultrastructural changes - Hojjatollah Shokri; Aghil Sharifzadeh (Shahrekord University of Medical Sciences, 2017)
Introduction: Zataria multiflora is a valuable medicinal plant from Lamiaceae family with various pharmacological and therapeutic properties. In this article we reviewed the various aspects of Z. multiflora properties including botanical characteristics, chemical composition, anti-fungal and anti-mycotoxin activity and fungal ultrastructural changes. Methods: Google Scholar, PubMed, EBSCO, Directory of open access journals (DOAJ), EMBASE, and Web of Science were searched using the keywords Z. multiflora and pathogenic and toxigenic fungi. Results: The essential oil (EO) of Z. multiflora is frequently used in pharmaceutical industries. Thymol and carvacrol are the most important active components of Z. multiflora that are used for the treatment of a wide variety of diseases such as candidiasis and dermatophytosis. Aflatoxin production inhibitory effect of Z. multiflora EO was at the transcription level and this herb may cause reduction in aflatoxin biosynthesis. Ultrastructural changes showed that the main sites of action of EO were the plasma membrane and cell wall of fungi. Conclusion: Zataria multiflora has the potential to be considered as a new natural drug for the treatment of some fungal infections. Morphological and structural changes may be one of the mechanisms involved in growth inhibition of the fungi and reducing aflatoxin production by Z. multiflora EO.